Modes of Esports Engagement in Overwatch - Ruotsalainen, Maria; Törhönen, Maria; Karhulahti, Veli-Matti (Springer Nature, 2022)
This Open Access book provides a comprehensive review of the rapidly developing esport phenomenon by examining one of its contemporary flagship titles, Overwatch (Blizzard Entertainment 2016), through three central themes and from a rich variety of research methods and perspectives. As a game with more than 40 million individual players, an annual international World Cup, and a franchised professional league with teams from Canada, China, Europe, South Korea, and the US, Overwatch provides a multifaceted perspective to the cultural, social, and economic topics associated with the development of esports, which has begun to attract attention from both commercial and academic audiences. The book starts with an introduction chapter to Overwatch and esports engagement in general, co-authored by the editors. This is followed by 15 unique chapters from scholars within the field of game cultures and esports, representing ten different nationalities. The contributions construct thematic sections that divide the book into three parts: Players, Diverse Audiences? and Fan & Fiction Work. As such, the parts provide a wide-ranging overview of esport engagement, thus disclosing the phenomenon's cross-cultural, transmedial, and interconnected relations that have not been probed earlier in a single anthology.